A Treasury in transition: changes and continuity in the management of Castilian State finances during the reign of Isabella I (1474-1504) - Ortego-Rico, Pablo (Palgrave Macmillan, 2023)
The aim of this chapter is to present a summary, an overview and comprehensive vision of the advances in research made in recent years in relation to the income and expenditure management structures implemented in the Kingdom of Castile during the reign of Isabella I (1474-1504). It is vitally important if we are to understand the transition from the late medieval tax and finance system to more complex systems, whose development allowed the Castilian monarchy to better achieve its political objectives and position itself at the beginning of the sixteenth century as one of the most powerful states, in tax and finance terms, in Western Europe.
Política de acceso abierto tomada de: https://www.routledge.com/our-products/open-access-books/publishing-oa-books/chapters
Keywords: Castilla (Reino) - Política fiscal; Castilla (Reino) - Administración; Castilla; Isabel I; Siglo XV; Hacienda Real; Instituciones políticas; Fiscalidad; Gestión hacendística; Tesoreros